The circumstances surrounding the currency stabilisation in Poland in the years 1918-1993 - Kowal, Stefan (Studia Historiae Oeconomicae, 2001)
The necessity for stabilisation of the Polish currency after the First World War arose a number of times. Particular reasons accounting for the development of situations leading to déstabilisation were different and manifold depending on their timing. In the inter-war period, the reasons and the results of the destabilisation of currency in Poland and in some other European countries were characterised by similar features. Satisfying the conditions to be fulfilled on the way to stabilisation lay within the sovereign decisions of the Polish state and, in the main, did not extend beyond the boundaries of the domestic economic policy of the country. Under those circumstances, it was possible that the introduction of necessary changes or the correction of the economic policy to attain or maintain the desired state of the currency brought results more easily. External factors, though significant, were not decisive.